2007
DOI: 10.1016/j.jada.2007.07.016
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Dietary Patterns in the Mexican-American Population and Their Association with Obesity

Abstract: Data from the National Health and Nutrition Examination Survey (NHANES) indicate that the trend toward increasing overweight and obesity among MexicanAmericans is continuing. This large population subgroup has a high prevalence of obesity and associated chronic conditions. Ethnic groups have different dietary patterns based on their geographical locations and various cultural influences. We examined the dietary patterns of Mexican-Americans and their association with total and central obesity. We hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
88
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 78 publications
12
88
1
1
Order By: Relevance
“…The latter system has been reported to overestimate whole grains intake, which concomitantly may result in underestimation of refined grains than when using the MyPyramid Equivalents Database (36) ; (ii) the present study included Mexican-American women only. In general, Hispanics have been reported to have higher dietary quality and consume more dietary fibre than individuals from other ethnic backgrounds (3,7,17) . Participants from both groups in the current study achieved the maximum score for total protein intake, as has been reported for the general US population (17,63) .…”
Section: Adequacy Components Of the Healthy Eating Index-2010mentioning
confidence: 99%
See 1 more Smart Citation
“…The latter system has been reported to overestimate whole grains intake, which concomitantly may result in underestimation of refined grains than when using the MyPyramid Equivalents Database (36) ; (ii) the present study included Mexican-American women only. In general, Hispanics have been reported to have higher dietary quality and consume more dietary fibre than individuals from other ethnic backgrounds (3,7,17) . Participants from both groups in the current study achieved the maximum score for total protein intake, as has been reported for the general US population (17,63) .…”
Section: Adequacy Components Of the Healthy Eating Index-2010mentioning
confidence: 99%
“…Poor dietary quality may be a major contributor to these disparities. Available surveillance data on dietary composition suggest that, as for other ethnic groups, the diet of Mexican-American adults is in need of improvement, as indicated by reports of high intakes of solid fats, cholesterol, added sugars and sugarsweetened beverages, and low intakes of vitamins D and E, Ca and K, whole grains, dairy products, dark greens and highly coloured vegetables (3)(4)(5)(6)(7) . Different ethnic subgroups have culture-bound patterns of food purchase, preparation and eating (8) , all of which can be affected by environmental resources (e.g.…”
mentioning
confidence: 99%
“…As to the second approach, cluster analysis (in groups) 10,11 and factorial analysis, or principal components analysis [12][13][14] , have been more frequently reported in literature. The main difference among them is that the cluster analysis gathers individuals, while the factorial analysis gathers variables.…”
Section: Introductionmentioning
confidence: 99%
“…Some epidemiological studies have shown an effect of sweetened beverages or fast-food consumption on BMI and waist circumference (WC) (26)(27)(28) . Some adolescent *Corresponding author: Email jvdbroeck1959@gmail.com r The Authors 2009 surveys have found a significant positive relationship between soft drink consumption and overweight (boys only) and obesity (23,29) , whereas others have not (19)(20)(21)(22) . The Westernized type of diet has become increasingly common among adolescents in developing countries and may be implicated in the emerging regional obesity epidemic.…”
mentioning
confidence: 99%